2022
DOI: 10.1002/da.23266
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal relationship between sensory impairments and depressive symptoms in older adults: The mediating role of functional limitation

Abstract: Background The underlying mechanism between sensory impairments (SIs) and depressive symptoms among Chinese older adults is not well understood. This study aims to explore the mediating role of functional limitation on the longitudinal relationship between SIs and depressive symptoms among older adults in China. Methods A total of 4130 older adults who participated in the 3‐year follow‐up China Health and Retirement Longitudinal Study (CHARLS) were included in the analysis. The hierarchical multiple linear reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…A cohort study revealed an association between altered sleep duration and depression ( 4 ). Depression is associated also with sensory impairment ( 29 , 30 ). In this study, we hypothesized that altered sleep duration would influence the risk of sensory impairment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cohort study revealed an association between altered sleep duration and depression ( 4 ). Depression is associated also with sensory impairment ( 29 , 30 ). In this study, we hypothesized that altered sleep duration would influence the risk of sensory impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Having a weak social network serves as a predictor of excessive sleep ( 42 ). If postretirement psychological changes are not addressed in a timely manner, this may lead to depression, which increases the risk of sensory impairment ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…These prevalence estimates were comparable with some previous China-based studies using similar tools to measure SI. One study reported a 58.6% prevalence of DSI among adults aged 45 years or older25; another study documented the prevalence of self-reported HI only, VI only and DSI in older Chinese adults being 5.7%, 22.2% and 58.6%, respectively;27 there was also literature focusing on long-lived individuals over 95 years of age in China and reported even higher prevalence among them: 66.1% of VI and 87.3% of HI 23. However, our estimates of SI prevalence seemed much higher than those reported in other studies from China (11.8% HI only, 6.3% VI only and 2.1% DSI28) and countries such as Korea (12.4% DSI29), Europe (eg, 34.4% either HI or VI, and 15.8% DSI in Germany30; 13.5% HI only, 10.2% VI only and 5.9% DSI in 11 European countries31), Canada (1.9% DSI32) and USA (24.4% HI only, 14.5% VI only and 18.2% DSI33).…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancies in prevalence rates across studies might be attributed to varieties in SI measurements (eg, self-reports or objective assessments) and participant characteristics (eg, age, race). The low use of assistive devices such as eyeglasses and hearing aids as well as the insufficient care priority paid to sensory problems may also contribute to the high prevalence of SI in China 25 27…”
Section: Discussionmentioning
confidence: 99%
“…Depressive symptoms were measured using CES-D which was a validated rating scale and had been widely used to assess depressive symptoms in the Chinese population ( 16 , 17 ). The CES-D includes 10 items that refer to depressive symptoms during the last week.…”
Section: Methodsmentioning
confidence: 99%